Desistance from crime. How much can be explained by life course transitions? - Torbjørn Skardhamar; Kjersti N. Aase (Statistics Norway, Research Department, 2014)
Objectives: Previous studies have argued that marriage, parenthood and employment are important factors that lead to desistance from crime. However, the effects of these events only apply to those experiencing them and do not necessarily explain why the majority of desisters stop offending. In this research note, we discuss how large a proportion of desisters experience these transitions. Methods: We describe changes in the lives of those who have stopped offending. We use data from a total population sample of all registered male offenders in Norway who committed at least five crimes in the past five years, and none thereafter (N=4963 persons). We report relevant life events from five years before until five years after the last recorded crime. Results: Of those who terminated their criminal career, 10 percent got married, 22 percent had a child, and 31 percent increased the number of months they were employed. In total, 47 percent experienced at least one of these events. Conclusions: While marriage, parenthood and employment are central to life course criminology, the majority of those who terminate a criminal career do so for other reasons.
Keywords: K00; 330; crime; desistance; family; employment; life-course